2011
DOI: 10.1016/j.ijrobp.2010.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic-Guided Dynamic Multileaf Collimator Tracking Enables Motion Management for Intensity-Modulated Arc Therapy

Abstract: Purpose-Intensity modulated arc therapy (IMAT) is attractive due to high dose conformality and efficient delivery. However, managing intrafraction motion is challenging for IMAT. The purpose of this research was to develop and investigate electromagnetic-guided DMLC tracking as an enabling technology to treat moving targets during IMAT.Materials/Methods-A real-time 3D DMLC-based target tracking system was developed and integrated with a linac. The DMLC tracking software inputs a real-time electromagnetically m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 36 publications
(39 reference statements)
1
86
0
Order By: Relevance
“…This study investigated two of the approaches for improved DMLC tracking accuracy suggested by Keall et al 15 and Poulsen et al:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study investigated two of the approaches for improved DMLC tracking accuracy suggested by Keall et al 15 and Poulsen et al:…”
Section: Discussionmentioning
confidence: 99%
“…4 The traces represented characteristic types of prostate motion: continuous drift, high frequency excursions, persistent excursion, and transient excursion. The traces are the same as in Keall et al 15 The traces started at isocenter. A dosimetric phantom was mounted on the motion platform (Delta4 with Hexamotion, Scandidos, Uppsala, Sweden).…”
Section: B Experimental Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The PTV structure was then overlaid to confirm tumour coverage based on beacon localisation. The patient was treated with Calypso-guided MLC tracking [23]. We utilise the kernel density estimation prediction algorithm [24] to account for the system's 220 ms latency [13].…”
Section: Mlc Tracking With Electromagnetic-guidancementioning
confidence: 99%
“…The investigation of the integration of electromagnetic transponder-guided MLC tracking on a Varian MLC has spanned several domains including geometric accuracy, 7 dosimetric fidelity, 8 quality assurance, 9 compatibility with volumetric modulated arc therapy (VMAT) (Ref. 10) and the ability to correct for in-plane rotation. 11 Note that the current study only corrects for real-time tumor translation and not real-time rotation.…”
Section: Introductionmentioning
confidence: 99%